Lithium iron phosphate material and preparation method thereof, positive pole piece, lithium battery and electric device
By designing the crystal structure and doping elements of lithium iron phosphate material, the problems of insufficient lithium ion transmission capacity, poor low temperature performance and poor cycle durability during charging and discharging of lithium iron phosphate material are solved, and the material is efficient Lithium ion diffusion, excellent magnification and low temperature performance, and long cycle life.
Patent Information
- Application Number
- CN202411455423.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-02-21
AI Technical Summary
During the charging and discharging process, existing lithium iron phosphate materials have problems such as insufficient lithium ion transmission capacity, poor low-temperature performance, and poor cycle durability.
By designing the crystal structure of lithium iron phosphate material, lithium ions diffuse in the radial direction, shorten the migration path of lithium ions, and adjust the microstructure of the material through doping elements to increase the electrochemical performance and safety of the material.
It improves the lithium ion diffusion rate and kinetic performance of lithium iron phosphate materials, enhances the rate performance and low temperature performance of the material, extends the cycle life of the battery and improves safety.
Smart Images

Figure CN119495743A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the technical field of batteries, and specifically, to lithium iron phosphate materials and preparation methods, positive electrode sheets, lithium batteries, and electrical devices. Background Art
[0002] As a highly regarded cathode material for lithium-ion batteries, lithium iron phosphate (LiFePO4) has made remarkable progress in the field of energy storage. Lithium iron phosphate materials have high safety due to their stable chemical composition and structural characteristics. During the charge and discharge process of the battery, the thermal stability and non-flammability of lithium iron phosphate significantly reduce the risk of battery thermal runaway. Lithium iron phosphate also has the advantage of relatively excellent structural stability, and the battery has high reliability during long-term use, reducing the maintenance and replacement costs of the battery. Although lithium iron phosphate materials have many above-mentioned advantages, they still face some challenges in the actual production and application process and still need further research and development. Summary of the Invention
[0003] In the first aspect of this application, a lithium iron phosphate material is proposed. The lithium iron phosphate material includes primary lithium iron phosphate grains, and the lithium iron phosphate material includes secondary lithium iron phosphate spherules composed of the primary lithium iron phosphate grains, and the primary lithium iron phosphate grains are arranged radially along the secondary lithium iron phosphate spherules.
[0004] The lithium iron phosphate material proposed in this application has a through structure in the radial direction. When lithium ions migrate, they can diffuse along the radial direction, shortening the lithium ion diffusion path and improving the migration ability of lithium ions, thereby increasing the lithium ion diffusion rate and kinetic performance of the lithium iron phosphate material. At the same time, the radially ordered structure can inhibit particle pulverization and particle breakage caused by intergranular cracks during the charge and discharge process, improving the long-cycle durability performance and safety performance.
[0005] In some embodiments, the D50 particle size of the lithium iron phosphate material is 3 μm - 8 μm. Thus, the lithium iron phosphate material is spherical-like particles with a D50 particle size within the aforementioned range.
[0006] In some embodiments, the chemical formula of the lithium iron phosphate material satisfies LiFe 1-x M x PO4, 0 < x ≤ 0.04, M is a doping element, and the doping element includes at least one of magnesium (Mg), titanium (Ti), niobium (Nb), tungsten (W), strontium (Sr), vanadium (V), rubidium (Rb). Thus, the lithium iron phosphate material has good electrochemical performance.
[0007] In some embodiments, the chemical formula of the lithium iron phosphate material satisfies LiFe 1-x M xPO4, 0.0015≤x≤0.04.
[0008] In some embodiments, the doping elements include at least two of Mg, Ti, Nb, W, Sr, V, and Rb. Thus, the doping elements can further adjust the microstructure of the lithium iron phosphate material during the crystallization process.
[0009] In some embodiments, the present invention further comprises: a coating layer, the coating layer is located on the outer surface of the lithium iron phosphate material, wherein the thickness of the coating layer is 2nm-10nm, thereby improving the electrochemical performance of the lithium iron phosphate.
[0010] In some embodiments, the mass of the coating layer accounts for 1wt%-2.5wt% of the mass of the lithium iron phosphate material. Thus, the lithium iron phosphate material has a higher active material loading.
[0011] In some embodiments, the material of the coating layer includes a carbon material, thereby improving the electronic conductivity of the lithium iron phosphate material.
[0012] In the second aspect of the present application, the present application proposes a method for preparing lithium iron phosphate material, comprising: mixing a complexing solution and a doping solution, and performing a crystal growth treatment to obtain a crystal nucleus solution, wherein the complexing solution includes ferrous salt, phosphoric acid, and a complexing agent, and the doping solution contains the doping element; mixing the crystal nucleus solution with a lithium salt to obtain a crystal slurry, wherein the crystal slurry contains the lithium iron phosphate material.
[0013] The method for preparing lithium iron phosphate proposed in the present application forms a complex with a chelating agent, a ferrous salt and phosphoric acid, and at the same time, adds doping elements to affect the crystallization process, controls the crystallization process and morphology of lithium iron phosphate, and helps to obtain lithium iron phosphate with radially growing crystal structure.
[0014] In some embodiments, in the complex solution, Fe 2+ With PO4 3- The molar ratio is (2.85-3.15): 2. This is conducive to the formation of Fe3(PO4)2 crystals.
[0015] In some embodiments, in the complex solution, Fe 2+ PO4 3- The sum of the molar concentrations of is 0.2 mol / L-1.0 mol / L. In the aforementioned concentration range, the formation of crystal nuclei in the crystal nucleus solution is facilitated.
[0016] In some embodiments, in the complexing solution, the molar addition amount of the complexing agent is about the same as the Fe 2+ PO4 3-The ratio of the sum of the molar addition amounts of is (2-3): 1. Within the aforementioned ratio range, the formed complex solution is more stable.
[0017] In some embodiments, in the crystal nucleus solution, Fe 2+ The molar ratio of the doping element to the lithium iron phosphate material is (95-100):(5-0.1). Thus, the doping element can affect the crystallization of the lithium iron phosphate material.
[0018] In some embodiments, the temperature of the crystal growth process is 50° C.-65° C., and the time of the crystal growth process is 9 h-15 h. Within the above temperature and time ranges, lithium iron phosphate crystals with a radial through structure can be prepared.
[0019] In some embodiments, the pH value of the environment for the crystal growth process is 2.0-4.0. Within the aforementioned pH value range, the crystal growth of lithium iron phosphate is favorable.
[0020] In some embodiments, in the crystal slurry, the lithium salt Li + The molar ratio of ferrous ion to ferrous ion is (0.98-1.08):1.
[0021] In some embodiments, the method further comprises: mixing the crystal nucleus solution with a reaction solution, wherein the reaction solution comprises an alcohol aqueous solution.
[0022] In some embodiments, the method further comprises: adding a phosphate supplement to the crystal slurry, wherein the molar ratio of phosphate in the phosphate supplement to ferrous ions in the crystal slurry is (1-1.1):1.
[0023] In the third aspect of the present application, the present application proposes a positive electrode plate, comprising: a positive electrode collector; a positive electrode active material layer, wherein the positive electrode active material layer is located on at least one side of the positive electrode collector, and the positive electrode active material layer comprises the lithium iron phosphate material.
[0024] The positive electrode plate proposed in the present application contains the lithium iron phosphate material proposed in the present application, and the battery system composed of the positive electrode plate ... has excellent rate performance and stable cycle performance.
[0025] In a fourth aspect of the present application, the present invention provides a lithium-ion battery comprising the positive electrode plate.
[0026] In some embodiments, the battery includes a positive electrode plate; the positive electrode plate includes a positive electrode collector and a positive electrode active material layer located on the surface of the positive electrode collector; the positive electrode active material layer includes a positive electrode material, a conductive agent and a binder, and the positive electrode active material includes the lithium iron phosphate material.
[0027] In some embodiments, the lithium battery can be prepared according to methods known in the technical field, and may include, for example, a negative electrode plate, a separator, an electrolyte, etc. The above-mentioned negative electrode plate, separator, and electrolyte can be selected according to methods known in the art and are not specifically limited in the present invention.
[0028] In a fifth aspect of the present application, the present invention proposes an electrical device, wherein the electrical device comprises the lithium battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0030] Figure 1 is the XRD structure diagram of the lithium iron phosphate of Example 1 of the present application;
[0031] Figure 2 is a SEM image of lithium iron phosphate of Example 1 of the present application;
[0032] Figure 3 is a schematic structural diagram of lithium iron phosphate in Example 1 of the present application;
[0033] Figure 4 This is the first charge and discharge curve of the button battery prepared with lithium iron phosphate in Example 1 of the present application;
[0034] Figure 5 This is a 25°C rate performance diagram of a soft-pack battery cell prepared with lithium iron phosphate in Example 1 of the present application;
[0035] Figure 6 This is the 45°C cycle capacity retention curve of the soft-pack battery prepared with lithium iron phosphate in Example 1 of the present application. DETAILED DESCRIPTION
[0036] The embodiments of the present application are described in detail below. Examples of the embodiments are shown in the drawings, but unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of actually identical structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0037] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; unless otherwise specified, the numerical values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).
[0038] The terms "including" and "having" in the specification and claims of the present application and any modifications thereof are open expressions, that is, including the contents specified in the present application but not excluding other contents.
[0039] In the description of this application, regardless of whether the words "about" or "approximately" are used, all the numbers disclosed herein are approximate values. The value of each number may differ by less than 10% or a reasonable difference considered by those skilled in the art, such as 1%, 2%, 3%, 4% or 5%.
[0040] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0041] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0042] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0043] The intrinsic structure of lithium iron phosphate is a one-dimensional channel diffusion path, and the lithium iron phosphate particles are composed of random crystal orientations of primary grains, which results in lithium ion transmission crossing more grain boundaries, causing greater diffusion resistance. The movement of lithium ions in the one-dimensional diffusion channel limits its lithium ion transmission capacity during rapid charge and discharge, and its deintercalation capacity is greatly limited, which in turn affects the high-rate charge and discharge performance. Under low temperature conditions, this limitation is more obvious, which in turn affects the low-temperature performance of lithium iron phosphate materials. At the same time, polycrystalline lithium iron phosphate composed of randomly arranged primary grains also has the phenomenon of unstable chemical levels and unstable mechanical properties. During the charge and discharge process of the battery, the anisotropy between lithium iron phosphate particles will lead to uneven stress distribution, which in turn causes microcracks to form inside the particles during long cycles. The cracks gradually extend from the inside of the particles to the surface, causing particle pulverization, aggravating the inactivation of the material and deteriorating the electrochemical performance. In addition, after the positive electrode material is prepared as a spherical material, it can be more densely stacked, which helps to improve the volume energy density of the battery. However, after lithium iron phosphate is prepared into a spherical shape, during the cycle process of a lithium battery in which it is used as the positive electrode material, the positive electrode material will undergo changes in mechanical and chemical properties, including phase changes in the positive electrode material structure, the generation of microcracks in the structure, and adverse reactions with the electrolyte, leading to a decrease in battery capacity and electrochemical performance.
[0044] In order to improve the deficiencies of the prior art, the present invention provides a lithium iron phosphate material and a preparation method, and a positive electrode plate. By designing the crystal structure of the lithium iron phosphate material, more lithium ion transmission channels are provided, and the transmission distance of lithium ions inside the material is reduced, thereby improving the rate discharge performance and low-temperature discharge characteristics of the lithium iron phosphate battery system.
[0045] In a first aspect of the present application, the present application proposes a lithium iron phosphate material, which includes lithium iron phosphate primary grains. The lithium iron phosphate material includes lithium iron phosphate secondary spheres composed of the lithium iron phosphate primary grains, and the lithium iron phosphate primary grains are arranged radially along the lithium iron phosphate secondary spheres.
[0046] The lithium iron phosphate material proposed in the present application has a through-channel structure formed by the arrangement of lithium iron phosphate primary grains in the radial direction. Lithium ions can diffuse radially when migrating, which shortens the migration path of lithium ions and reduces the resistance encountered during migration. Therefore, the migration ability of lithium ions is improved, thereby improving the lithium ion diffusion rate and kinetic performance of the lithium iron phosphate material. The ordered structure of the lithium iron phosphate arranged in the radial direction is conducive to inhibiting the generation of intergranular cracks caused by lattice contraction / expansion of the lithium iron phosphate material during the charging and discharging process. At the same time, the lithium iron phosphate material with a radial arrangement structure has a relatively consistent lattice orientation, thereby improving the structural stability and safety by alleviating the internal stress concentration of the lithium iron phosphate material caused by phase change.
[0047] In some embodiments, the particle size D50 of the lithium iron phosphate material is 3 μm - 8 μm. Thus, the lithium iron phosphate material is spherical-like particles with a particle size D50 within the aforementioned range. Within the aforementioned particle size D50 range, the migration path of lithium ions is shorter.
[0048] In some embodiments, the chemical formula of the lithium iron phosphate material satisfies LiFe 1-x M x PO4, 0 < x ≤ 0.04, where M is a doping element, and the doping element includes at least one of magnesium (Mg), titanium (Ti), niobium (Nb), tungsten (W), strontium (Sr), vanadium (V), and rubidium (Rb). Thus, the doping element can inhibit the growth of the lithium iron phosphate unit cell. After doping with the doping element, the volume of the primary grains of lithium iron phosphate decreases, shortening the migration path of lithium ions. Therefore, the lithium iron phosphate material has good electrochemical performance.
[0049] In some embodiments, the chemical formula of the lithium iron phosphate material satisfies LiFe 1-x M x PO4, 0.0015 ≤ x ≤ 0.04. Thus, the doping ions can better regulate the crystal of lithium iron phosphate.
[0050] In some embodiments, the doping element includes at least two of Mg, Ti, Nb, W, Sr, V, and Rb. Thus, the low-valent metal elements in the doping elements are evenly distributed throughout the lithium iron phosphate material because the low-valent metals with smaller atoms and lighter masses can be easily incorporated into the bulk structure to play a role in stabilizing the main structure; while the high-valent metal elements in the doping elements can effectively inhibit the coarsening of the primary grains of lithium iron phosphate, inhibit the growth of the primary grains and keep their microstructure morphology of secondary spherules, playing a role in maintaining the particle morphology and regulating the primary particle size. Therefore, the doping element can further regulate the microstructure of the lithium iron phosphate material during the crystallization process.
[0051] In some embodiments, it further includes: a coating layer, which is located on the outer surface of the lithium iron phosphate material. Among them, the thickness of the coating layer is 2 nm - 10 nm. Thus, the coating layer provides a layered structure with high electronic conductivity on the outer surface of the lithium iron phosphate material, improving the electrochemical performance of the lithium iron phosphate.
[0052] In some embodiments, the mass of the coating layer accounts for 1 wt% - 2.5 wt% of the mass of the lithium iron phosphate material. Thus, the mass of the lithium iron phosphate with a primary grain radial structure in the lithium iron phosphate material accounts for 97.5 wt% - 99.0 wt% of the total mass, and the lithium iron phosphate material has a high active material loading.
[0053] In some embodiments, the material of the coating layer includes a carbon material. Thus, the lithium iron phosphate materials can form a three-dimensional conductive network interconnected with each other, which can improve the electronic conductivity of the lithium iron phosphate material.
[0054] In the second aspect of the present application, the present application proposes a method for preparing lithium iron phosphate material, comprising: mixing a complexing solution and a doping solution, and performing a crystal growth treatment to obtain a crystal nucleus solution, wherein the complexing solution includes ferrous salt, phosphoric acid, and a complexing agent, and the doping solution contains the doping element; mixing the crystal nucleus solution with a lithium salt to obtain a crystal slurry, wherein the crystal slurry contains the lithium iron phosphate material.
[0055] The method for preparing lithium iron phosphate proposed in this application forms a complex with a ferrous salt and phosphoric acid through a chelating agent, and at the same time, adds doping elements to affect the crystallization process, controls the process and morphology of lithium iron phosphate crystallization, and makes it have a secondary spherical stacking polymorph. Among them, its primary grains grow in a radially oriented arrangement, and the lithium iron phosphate grains formed by the radial growth of the particles are continuously penetrated in the radial direction, and lithium ions can diffuse directly from the center of the particles to the surface of the particles. The migration path distance of lithium ions is shortened, the diffusion migration resistance is reduced, and the deintercalation and embedding and ion migration capabilities of lithium ions are improved, so the first charge and discharge coulomb efficiency, rate performance and low temperature performance of lithium batteries are improved. The preparation process of this method is simple, the production cost is low, the environment is friendly, and it can be applied to industrial mass production and promotion. The lithium iron phosphate material prepared by this method can be applied to the battery system to show good comprehensive performance, especially excellent low temperature performance, rate performance and cycle performance.
[0056] In some embodiments, in the complex solution, Fe 2+ With PO4 3- The molar ratio of Fe is (2.85-3.15):2. 2+ With PO4 3- The molar ratio of Fe in lithium iron phosphate crystals 2+ With PO4 3- The molar ratio is close, which is conducive to the formation of Fe3(PO4)2 crystals.
[0057] In some embodiments, in the complex solution, Fe 2+ PO4 3- The sum of the molar concentrations of Fe 2+ With PO4 3- It can form complex molecules of a certain concentration with the complexing agent. The complex molecules move freely in the solution and collide and combine with each other, which is conducive to the formation of crystal nuclei in the crystal nucleus solution.
[0058] In some embodiments, in the complexing solution, the molar addition amount of the complexing agent is about the same as the Fe 2+ PO4 3- The ratio of the sum of the molar addition amounts of Fe and Fe is (2-3):1. Within the above ratio range, the complexing agent in the complexing solution is slightly excessive, and there may be Fe 2+ PO4 3- The combined complexing agent molecules make Fe 2+ PO4 3- The chance of individual combination and crystallization is reduced, and the formed complex solution is more stable.
[0059] As an example, the molar addition amount of the complexing agent is about the same as that of the Fe 2+ PO4 3- The ratio of the sum of the molar addition amounts of the complexing agent and Fe can be 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, 3:1. 2+ PO4 3- It can form complex molecules with relatively consistent structures. During the crystallization process, the complex molecules can be arranged radially to control the structure of the crystal.
[0060] In some embodiments, the pH value of the complexing solution is 2.0-4.0.
[0061] In some embodiments, the complexing solution includes an acid solution for adjusting the pH value of the complexing solution, wherein the solute of the acid solution includes acetic acid. Thus, the acid solution can adjust the pH value of the crystallization process but does not participate in the chemical reaction.
[0062] In some embodiments, in the crystal nucleus solution, Fe 2+ The molar ratio of the doping element to the lithium iron phosphate material is (95-100): (5-0.1). Thus, the doping element can affect the crystallization of the lithium iron phosphate material. At the same time, within the aforementioned doping amount range, the electrochemically inert doping element has a limited effect on the electrochemical properties of the lithium iron phosphate, while its effect on the crystal structure of the lithium iron phosphate is relatively ideal, and can inhibit the growth of the lithium iron phosphate cell caused by crystal melting.
[0063] In some embodiments, the complexing agent includes at least one of citric acid, tartaric acid, and oxalic acid. 2+ PO4 3- The formation of complex molecules helps the crystallization process to occur in an orderly and radial direction. After the lithium iron phosphate crystals are formed, the complexing agent can be removed by heating, which is a simple method and will not cause other effects on the lithium iron phosphate crystals.
[0064] In some embodiments, the solute of the doping solution includes at least one of a chloride salt of the doping element and a sulfate salt of the doping element. The doping element is introduced into the doping solution by using the aforementioned salt containing the doping element, and the doping element forms a complex molecule with the complexing agent in the form of a metal cation. The carboxyl group in the complexing agent and the metal cation form a 7-membered or 8-membered chelate ring, and the chloride and sulfate anions do not participate in the crystallization process.
[0065] In some embodiments, the temperature condition of the crystal growth treatment is 50°C-65°C, and the time of the crystal growth treatment is 9h-15h. The temperature condition is within the aforementioned range, which is conducive to the activity and selectivity of the reaction, so that the reactants can be effectively converted into the target product, while suppressing the occurrence of overreaction or side reactions. In addition, it is also conducive to controlling the reaction rate and the purity of the product. The time of the crystal growth treatment is within the aforementioned range, combined with the reaction rate under the aforementioned control, which is conducive to the full progress of the crystal growth process.
[0066] In some embodiments, the crystal growth process may be stirred at a speed of 250 rpm to 350 rpm. The stirring speed within the aforementioned range may control the crystal nucleation rate and growth rate, so that the lithium iron phosphate grains in the nucleation and growth process form a denser structure.
[0067] In some embodiments, the pH value of the environment for the crystal growth process is 2.0-4.0. Within the aforementioned pH value range, the crystal growth of lithium iron phosphate is favorable.
[0068] As an example, the pH value of the environment of the crystal growth process can be 2.0, 2.1, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0.
[0069] In some embodiments, the protective atmosphere of the crystal growth process includes at least one of nitrogen and an inert gas.
[0070] Under the aforementioned crystal growth treatment conditions, the oxidation of ferrous ions is prevented by a protective atmosphere, the stability of the complex molecules is maintained under acidic conditions, the stirring treatment promotes the movement of ions and molecules in the solution to achieve more uniform crystallization in all directions, and the alcohol aqueous solution provides a stable environment suitable for crystallization, thereby promoting ferrous ions and phosphate to form Fe3(PO4)2 crystals with a radial structure, thereby helping to obtain lithium iron phosphate with a radially grown crystal structure.
[0071] In some embodiments, in the crystal slurry, the lithium salt Li +The molar ratio of ferrous ions to ferrous ions is (0.98-1.08): 1. Lithium ions are introduced into the crystal nucleus solution by adding lithium salt to obtain a crystal slurry capable of generating lithium iron phosphate crystals. In the crystal slurry, after the lithium salt is added, the lithium ions enter the Fe3(PO4)2 crystals that have formed a radial structure, and the Fe3(PO4)2 crystals are transformed into lithium iron phosphate crystals.
[0072] In some embodiments, the method further comprises: mixing the crystal nucleus solution with a reaction solution, wherein the reaction solution comprises an alcohol aqueous solution.
[0073] In some embodiments, the method further comprises: adding a phosphate supplement to the crystal slurry, wherein the molar ratio of phosphate in the phosphate supplement to ferrous ions in the crystal slurry is (1-1.1): 1. Thus, by controlling the molar ratio of iron to phosphate in the crystal slurry to be close to the molar ratio of iron to phosphate in lithium iron phosphate, the conversion of Fe3(PO4)2 crystals to lithium iron phosphate crystals is facilitated.
[0074] In some embodiments, the lithium salt includes at least one of lithium carbonate and lithium hydroxide.
[0075] In some embodiments, a crystal slurry containing lithium iron phosphate crystals is spray dried with an inlet temperature of 180°C-240°C and an outlet temperature of 90°C-130°C to obtain LiFePO4 powder with a particle size D50 of 3μm-8μm and a water mass fraction of ≤1.5%.
[0076] In some embodiments, the method further comprises a sintering treatment, wherein the sintering treatment comprises mixing the lithium iron phosphate with a carbon source, the sintering treatment temperature is 600° C.-800° C., and the sintering treatment time is 3 h-12 h.
[0077] Through sintering treatment, on the one hand, a carbon coating layer is formed on the surface of lithium iron phosphate through the coating of carbon source to improve the conductive properties of lithium iron phosphate material; on the other hand, under the high temperature conditions of sintering treatment, the complexing agent molecules mixed in the crystal can be decomposed, and some carbon atoms after the decomposition of the complexing agent can form a carbon coating layer together with the carbon source, and some carbon atoms are vaporized at high temperature and separated from the lithium iron phosphate.
[0078] In some embodiments, the carbon source is glucose, and glucose and LiFePO4 are prepared in a mass ratio of (0.02-0.08):1.
[0079] In some embodiments, the sintering process is performed in a nitrogen atmosphere with multiple stages of temperature-controlled sintering, with the temperature rising from room temperature to 500-600°C at a heating rate of 2°C / min-5°C / min and kept at that temperature for 3h-5h, then rising to 600-800°C and kept at that temperature for 8h-12h; and then naturally cooling to room temperature.
[0080] In the third aspect of the present application, the present application proposes a positive electrode plate, comprising: a positive electrode collector; a positive electrode active material layer, wherein the positive electrode active material layer is located on at least one side of the positive electrode collector, and the positive electrode active material layer comprises the lithium iron phosphate material.
[0081] The positive electrode plate proposed in the present application contains the lithium iron phosphate material proposed in the present application, which has excellent rate performance and long cycle durability.
[0082] In some embodiments, lithium iron phosphate material, conductive carbon black SP and polyvinylidene fluoride resin (PVDF) are weighed and uniformly mixed in a mass ratio of 95:3:2, and dispersed with N-methylpyrrolidone (NMP) solvent to form a slurry; the slurry is uniformly coated on a carbon-coated aluminum foil and placed in an oven for baking at 80°C. After high-temperature drying for 12 hours, a positive electrode sheet is obtained. The dried positive electrode sheet is rolled and cut into round sheets and placed in a glove box for standby use. The above-prepared wafer was used as the positive electrode, metallic lithium as the negative electrode, a microporous polypropylene film (Celgard 2500) as the separator, 1.1 mol / L LiPF6, ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a mass ratio of EC:EMC:DMC=1:1:1, and 1.5% vinylene carbonate (VC) additive as the electrolyte to assemble a 2032-type button battery. The lithium-ion battery assembly process must be carried out in a glove box using argon as the protective gas.
[0083] In some embodiments, the prepared lithium iron phosphate material is used as the positive electrode material, artificial graphite is used as the negative electrode material, commercial electrolyte, and separator are assembled into soft-pack batteries in a lithium-ion battery production line, wherein the positive electrode plate comprises: lithium iron phosphate material, conductive carbon black and binder polyvinylidene fluoride resin (PVDF-HSV900) are evenly mixed in a mass ratio of 96.0:1.5:2.5, and N-methylpyrrolidone (NMP) is used as the solvent. The slurry is evenly stirred to obtain the slurry and then coated on an aluminum foil current collector. The positive electrode current collector is 12μm+2μm (12μm substrate and 2μm carbon-coated layer) carbon-coated aluminum foil; the plate is rolled into sheets after high-temperature baking, and cut into positive electrode sheets for standby use. The negative electrode sheet includes: artificial graphite, conductive agent, sodium carboxymethyl cellulose (CMC) and binder styrene butadiene rubber latex (SBR) are uniformly mixed in a mass ratio of 95.5:1.0:1.5:2, and the solvent is deionized water. After stirring evenly to obtain a slurry, it is coated on the copper foil current collector, and the negative electrode current collector is 8μm copper foil; and cut into negative electrode sheets for use. The electrolyte standard is 1mol / L LiPF6 (EC:EMC=1:2)+additives; the diaphragm is a 9μm+3μm (9μm substrate and 3μm coating) mixed diaphragm (including: substrate, PVDF, ceramic mixed coating).
[0084] In a fourth aspect of the present application, the present invention provides a lithium-ion battery comprising the positive electrode plate.
[0085] In some embodiments, the battery includes a positive electrode plate; the positive electrode plate includes a positive electrode collector and a positive electrode active material layer located on the surface of the positive electrode collector; the positive electrode active material layer includes a positive electrode material, a conductive agent and a binder, and the positive electrode active material includes the lithium iron phosphate material.
[0086] In some embodiments, the lithium battery can be prepared according to methods known in the technical field, and may include, for example, a negative electrode plate, a separator, an electrolyte, etc. The above-mentioned negative electrode plate, separator, and electrolyte can be selected according to methods known in the art and are not specifically limited in the present invention.
[0087] In a fifth aspect of the present application, the present invention proposes an electrical device, wherein the electrical device comprises the lithium battery.
[0088] The scheme of the present application is described below by specific examples. It should be noted that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this area or the product instructions are used. The reagents or instruments used are not specified by the manufacturer, and are all conventional products that can be obtained commercially.
[0089] Example 1
[0090] 1. Preparation of positive electrode materials
[0091] S100: Preparation of reaction solution
[0092] A mixed solvent of ethylene glycol and deionized water was prepared as the reaction base liquid, wherein the volume ratio of deionized water to ethylene glycol was 1:1, and an aqueous solution of FeSO4 and H3PO4 was prepared as the reaction liquid, and the solute concentration was 0.5 mol / L, wherein Fe in the soluble ferrous salt was 2+ PO4 in soluble compounds containing phosphate ions 3- The molar ratio of 3:2 is 3:2; the citric acid aqueous solution is used as the complexing agent solution, and its molar concentration is 0.2mol / L; the acetic acid aqueous solution is used as the acid solution, and its molar concentration is 1.5mol / L; the LiOH aqueous solution is used as the lithium source solution, and its molar concentration is 0.4mol / L; the (NH4)H2PO4 aqueous solution is used as the phosphorus source solution, and its molar concentration is 0.5mol / L. The doping solution is MgCl2 and NbCl5, and the Mg in the doping solution is 2+ With Nb 5+ The molar ratio is 2:1.
[0093] S200: Crystal growth process
[0094] The reaction base liquid, complexing agent solution and acid solution are added to the reactor in sequence, the reaction temperature is set to 55°C, the solution pH is set to 2.6, and high-purity N2 is continuously bubbled into the reaction process to remove oxygen in the solution; FeSO4 and H3PO4 reaction solutions are gradually added, the amount of acid solution added is fine-tuned to control the reaction pH, and the stirring speed is set to 250rpm. The process is the nucleation and growth of Fe3(PO4)2 crystals. The reaction is terminated after the median particle size D50 of the particles reaches 5.0um.
[0095] S300: Preparation of lithium iron phosphate slurry
[0096] LiOH solution, (NH4)H2PO4 solution and mixed solution were gradually added to the reactor, wherein Li in the soluble LiOH + Add molar amount equal to Fe in Fe3(PO4)2 2+ The molar ratio is 3.18:1, Fe 2+ Content and (Mg 2+ +Nb 5+ ) content molar ratio is 99.6:0.4, and the reaction is continued for 5 hours to obtain a product slurry.
[0097] S400: Preparation of lithium iron phosphate precursor
[0098] The crystal slurry obtained in S300 is spray dried, and the temperature of the feed port is controlled to be 200° C. and the temperature of the discharge port is controlled to be 100° C. to obtain LiFePO4 precursor powder.
[0099] S500: Sintering treatment
[0100] The LiFePO4 precursor powder obtained by S400 was mixed with glucose, and calcined at a high temperature in a nitrogen atmosphere at a mass ratio of glucose to LiFePO4 of 0.04:0.96. The temperature was increased from room temperature to 520°C at a heating rate of 3°C / min and kept for 3 hours, then increased to 750°C and kept for 10 hours; after naturally cooling to room temperature, LiFePO4 / C particles were obtained.
[0101] Example 2
[0102] 1. Preparation of positive electrode materials
[0103] S100: Preparation of reaction solution
[0104] A mixed solvent of polyethylene glycol 200 and deionized water was prepared as the reaction base liquid, wherein the volume ratio of deionized water to polyethylene glycol 200 was 2:1, and an aqueous solution of FeC2O4 and H3PO4 was prepared as the reaction liquid, and the solute concentration was 0.4 mol / L, wherein Fe in the soluble ferrous salt was 2+ PO4 in soluble compounds containing phosphate ions 3- The molar ratio of 3:2 is 3:2; the oxalic acid aqueous solution is used as the complexing agent solution, and its molar concentration is 0.5mol / L; the acetic acid aqueous solution is used as the acid solution, and its molar concentration is 3.0mol / L; the LiOH aqueous solution is used as the lithium source solution, and its molar concentration is 0.3mol / L; the (NH4)H2PO4 aqueous solution is used as the phosphorus source solution, and its molar concentration is 0.3mol / L. The doping solution is MgCl2 and WCl5, and the Mg in the doping solution is 2+ With W 5+ The molar ratio is 2:1.
[0105] S200: Crystal growth process
[0106] The reaction base liquid, complexing agent solution and acid solution are added to the reactor in sequence, the reaction temperature is set to 58°C, the solution pH is set to 3.0, and high-purity N2 is continuously bubbled into the reaction process to remove oxygen in the solution; FeSO4 and H3PO4 reaction solutions are gradually added, the amount of acid solution added is fine-tuned to control the reaction pH, and the stirring speed is set to 275rpm. The process is the nucleation and growth of Fe3(PO4)2 crystals. The reaction is terminated after the median particle size D50 of the particles reaches 5.5um.
[0107] S300: Preparation of lithium iron phosphate slurry
[0108] LiOH solution, (NH4)H2PO4 solution and mixed solution were gradually added to the reactor, wherein Li in the soluble LiOH + Add molar amount equal to Fe in Fe3(PO4)2 2+ The molar ratio is 3.24:1, Fe 2+ Content and (Mg 2+ +Nb 5+ ) content molar ratio is 99.7:0.3, and the reaction is continued for 4 hours to obtain a product slurry.
[0109] S400: Preparation of lithium iron phosphate precursor
[0110] The crystal slurry obtained in S300 is spray dried, and the temperature of the feed port is controlled to be 200° C. and the temperature of the discharge port is controlled to be 100° C. to obtain LiFePO4 precursor powder.
[0111] S500: Sintering treatment
[0112] The LiFePO4 precursor powder obtained by S400 was mixed with sucrose, and calcined at a high temperature in a nitrogen atmosphere at a mass ratio of sucrose to LiFePO4 of 0.05:0.95. The temperature was increased from room temperature to 520°C at a heating rate of 3°C / min and kept for 3 hours, then increased to 750°C and kept for 8 hours; after naturally cooling to room temperature, LiFePO4 / C particles were obtained.
[0113] Example 3
[0114] 1. Preparation of positive electrode materials
[0115] S100: Preparation of reaction solution
[0116] A mixed solvent of polyethylene glycol 400 and deionized water was prepared as the reaction base liquid, wherein the volume ratio of deionized water to polyethylene glycol was 2:1, and an aqueous solution of FeSO4 and H3PO4 was prepared as the reaction liquid, and the solute concentration was 0.5 mol / L, wherein Fe in the soluble ferrous salt was 2+ PO4 in soluble compounds containing phosphate ions 3- The molar ratio of is 3:2; the citric acid aqueous solution is used as the complexing agent solution, and its molar concentration is 0.2mol / L; the acetic acid aqueous solution is used as the acid solution, and its molar concentration is 1.5mol / L; the Li2CO3 aqueous solution is used as the lithium source solution, and its molar concentration is 0.4mol / L; the (NH4)H2PO4 aqueous solution is used as the phosphorus source solution, and its molar concentration is 0.5mol / L. The doping solution is SrSO4 and VCl5, and the Sr in the doping solution is 2+ With V 5+ The molar ratio is 2:1.
[0117] S200: Crystal growth process
[0118] The reaction base liquid, complexing agent solution and acid solution are added into the reactor in sequence, the reaction temperature is set to 60°C, the solution pH is set to 2.6, and high-purity N2 is continuously bubbled into the reaction process to remove oxygen in the solution; FeSO4 and H3PO4 reaction solutions are gradually added, the amount of acid solution added is fine-tuned to control the reaction pH, and the stirring speed is set to 320 rpm. The process is the nucleation and growth of Fe3(PO4)2 crystals. The reaction is terminated after the median particle size D50 of the particles reaches 5.2 um.
[0119] S300: Preparation of lithium iron phosphate slurry
[0120] LiOH solution, (NH4)H2PO4 solution and mixed solution were gradually added to the reactor, among which Li in soluble Li2CO3 + Add molar amount equal to Fe in Fe3(PO4)2 2+ The molar ratio is 3.21:1, Fe 2+ Content and (Sr 2+ +V 5+ ) content molar ratio is 99.6:0.4, and the reaction is continued for 5 hours to obtain a product slurry.
[0121] S400: Preparation of lithium iron phosphate precursor
[0122] The crystal slurry obtained in S300 is spray dried, and the temperature of the feed port is controlled to be 200° C. and the temperature of the discharge port is controlled to be 100° C. to obtain LiFePO4 precursor powder.
[0123] S500: Sintering treatment
[0124] The LiFePO4 precursor powder obtained by S400 was mixed with sucrose, and calcined at a high temperature in a nitrogen atmosphere at a mass ratio of sucrose to LiFePO4 of 0.04:0.96. The temperature was raised from room temperature to 500°C at a heating rate of 3°C / min and kept for 3 hours, then raised to 740°C and kept for 10 hours; after naturally cooling to room temperature, LiFePO4 / C particles were obtained.
[0125] Comparative Example 1
[0126] 1. Preparation of positive electrode materials
[0127] S100: Preparation of reaction solution
[0128] A mixed solvent of ethylene glycol and deionized water was prepared as the reaction base liquid, wherein the volume ratio of deionized water to ethylene glycol was 1:1, and an aqueous solution of LiOH, FeSO4 and H3PO4 was prepared as the reaction liquid, and the solute concentration was 0.6 mol / L, wherein Li in the soluble LiOH +Fe in soluble ferrous salts 2+ and PO4 in soluble compounds containing phosphate ions 3- The molar ratio of MgCl2 and TiCl4 is 1.06:1:1; the molar concentration of citric acid aqueous solution is 0.3 mol / L as the complexing agent solution; the molar concentration of acetic acid aqueous solution is 2.5 mol / L as the acid solution. 2+ With Ti 4+ The molar ratio is 1:1.
[0129] S200: Crystal growth process
[0130] The reaction base liquid, complexing agent solution and acid solution are added to the reactor in sequence, the reaction temperature is set to 55°C, the solution pH is set to 2.6, and high-purity N2 is continuously bubbled into the reaction process to remove oxygen in the solution; LiOH, FeSO4 and H3PO4 reaction solutions are gradually added, the amount of acid solution added is fine-tuned to control the reaction pH, the stirring speed is set to 280 rpm, the process is the nucleation and growth of LiFePO4 crystals, and the reaction is terminated after the reaction continues until the median particle size D50 of the particles reaches 5.8 um.
[0131] S300: Preparation of lithium iron phosphate precursor
[0132] The crystal slurry obtained in S200 is spray dried, and the temperature of the feed port is controlled to be 200° C. and the temperature of the discharge port is controlled to be 100° C. to obtain LiFePO4 precursor powder.
[0133] S400: Sintering treatment
[0134] The LiFePO4 precursor powder obtained by S300 was mixed with glucose, and calcined at a high temperature in a nitrogen atmosphere at a mass ratio of glucose to LiFePO4 of 0.03:0.97. The temperature was increased from room temperature to 520°C at a heating rate of 3°C / min and kept for 3 hours, then increased to 760°C and kept for 10 hours; after naturally cooling to room temperature, LiFePO4 / C particles were obtained.
[0135] Test method:
[0136] 1. Discharge capacity test
[0137] S1: Button battery assembly
[0138] Preparation of lithium iron phosphate material into 2032 button battery
[0139] S2: Test discharge capacity
[0140] 1) Carry out charging performance test at 25±5℃, and activate the assembled button cell for 24h;
[0141] 2) 0.1C constant current charging to the upper limit voltage of 3.7V, then constant voltage charging, cut-off current 0.025C; rest for 10 minutes;
[0142] 3) 0.1C constant current discharge to 2.2V, rest for 10 minutes; first charge and discharge efficiency = first discharge gram capacity / first charge gram capacity;
[0143] 4) Repeat steps 2) and 3) to perform charge and discharge tests, and take the average value as the discharge gram capacity result.
[0144] 2. Rate performance test
[0145] S1: Soft pack battery preparation
[0146] The prepared lithium iron phosphate material is used as the positive electrode material to prepare the soft pack battery
[0147] S2: Test rate performance
[0148] The rate performance test was carried out at a temperature of 25℃±2℃, with a voltage range of 2.2V-3.65V. The test process is as follows:
[0149] 1) Perform capacity test at 1C / 1C cycle three times at 25±2℃ to obtain the discharge capacity value of the battery cell;
[0150] 2) Discharge at 0.33C to the lower limit voltage of 2.2V and let stand for 10 minutes;
[0151] 3) Charge at a constant current of 0.33C to an upper voltage of 3.65V, then charge at a constant voltage, with a cut-off current of 0.05C, and let stand for 10 minutes;
[0152] 4) Discharge at nC to the lower limit voltage of 2.2V, where nC = 1C / 2C / 3C / 4C;
[0153] 5) Repeat steps 3) and 4) to complete discharge at all rates.
[0154] 3. Cyclic capacity test
[0155] S1: Soft pack battery preparation
[0156] The prepared lithium iron phosphate material is used as the positive electrode material to prepare the soft pack battery
[0157] S2: Test cycle capacity
[0158] The cycle capacity retention rate test was carried out at 25℃±2℃ and 45℃±2℃ respectively. The state voltage, internal resistance, thickness and DC internal resistance of the soft-pack battery were tested. The voltage range was 2.2V-3.65V. The test process included:
[0159] 1) The battery cell is placed in an environment of 25℃±2℃ (or 45℃±2℃) and the 1C / 1C cycle is performed three times for capacity testing to obtain the discharge capacity of the battery cell;
[0160] 2) 1C discharge to the lower limit voltage, let stand for 10 minutes;
[0161] 3) Charge at 1C to the upper voltage limit, with a cut-off rate of 0.05C, and let stand for 10 minutes;
[0162] 4) 1C discharge to the lower limit voltage, let stand for 30 minutes;
[0163] 5) Repeat steps 3) and 4) for n rounds.
[0164] After n cycles of 1C / 1C (n≤5000), the cycle capacity retention rate of the battery is calculated. The first cycle test capacity is recorded as A1, and the test capacity after n cycles is recorded as An. The capacity retention rate = An / A1×100%.
[0165] 4.EIS impedance value test - AC impedance method test
[0166] Electrochemical impedance spectroscopy (EIS) measurements were performed on a Gamry Reference 600 electrochemical workstation. The assembled soft-pack cells were tested with the battery state adjusted to 50% SOC, an amplitude of 5 mV, and a frequency range of 10 -2 Hz-10 5 Hz.
[0167] Test results: see Table 1
[0168] Table 1
[0169]
[0170] It can be seen from the test results in Table 1 that compared with Comparative Example 1, the discharge capacity in grams, first charge and discharge efficiency, rate discharge capacity retention rate, 25°C cycle capacity retention rate, and 45°C cycle capacity retention rate of the batteries prepared from the lithium iron phosphate materials of Examples 1 to 3 have all increased, and the EIS impedance value has decreased.
[0171] In the description of the present application, "A and / or B" may include the case of A alone, the case of B alone, or any of the cases of A and B, where A and B are only used for examples and may be any technical feature connected by "and / or" in the present application.
[0172] In the description of this application, "same chemical composition" should be understood in a broad sense, that is, the main components of the two have the same chemical composition, or the chemical composition of the two is basically the same, and may have errors within the allowable range in the field that are understandable to those skilled in the art or contain impurities within the allowable range.
[0173] In the present application, the writing order of each step does not mean a strict execution order and does not constitute any limitation on the implementation process. The specific execution order of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0174] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A lithium iron phosphate material, characterized in that: The lithium iron phosphate material includes lithium iron phosphate primary grains, the lithium iron phosphate material includes lithium iron phosphate secondary spheres formed by the lithium iron phosphate primary grains, and the lithium iron phosphate primary grains are arranged along the radial direction of the lithium iron phosphate secondary spheres.
2. The lithium iron phosphate material according to claim 1, characterized in that: The particle size D50 of the lithium iron phosphate material is 3 μm-8 μm; and / or, The chemical formula of the lithium iron phosphate material satisfies LiFe 1-x M x PO4, where 0 < x ≤ 0.04, M is a doping element, and the doping element includes at least one of Mg, Ti, Nb, W, Sr, V, and Rb.
3. The lithium iron phosphate material according to claim 2, characterized in that: The chemical formula of the lithium iron phosphate material satisfies LiFe 1-x M x PO4, 0.0015≤x≤0.04; and / or, The doping elements include at least two of Mg, Ti, Nb, W, Sr, V, and Rb.
4. The lithium iron phosphate material according to any one of claims 1 to 3, characterized in that: Further including: A coating layer is located on the outer surface of the lithium iron phosphate material, wherein the coating layer has a thickness of 2nm-10nm, and the material of the coating layer includes a carbon material.
5. The lithium iron phosphate material according to claim 4, characterized in that: The mass of the coating layer accounts for 1wt%-2.5wt% of the mass of the lithium iron phosphate material.
6. A method for preparing the lithium iron phosphate material according to any one of claims 1 to 3, characterized in that: include: Mixing a complexing solution and a doping solution, and performing a crystal growth process to obtain a crystal nucleus solution, wherein the complexing solution comprises ferrous salt, phosphoric acid, and a complexing agent, and the doping solution comprises the doping element; The crystal nucleus solution is mixed with a lithium salt to obtain a crystal slurry, wherein the crystal slurry contains the lithium iron phosphate material.
7. The method according to claim 6, characterized in that In the complex solution, Fe 2+ With PO4 3- The molar ratio is (2.85-3.15):2; and / or, In the complex solution, Fe 2+ PO4 3- The sum of the molar concentrations is 0.2 mol / L-1.0 mol / L; and / or, In the complexing solution, the molar addition amount of the complexing agent is equal to the molar addition amount of the Fe 2+ PO4 3- The ratio of the sum of the molar addition amounts is (2-3):1; and / or, In the crystal nucleus solution, Fe 2+ The molar ratio of the doping element is (95-100):(5-0.1).
8. The method according to claim 6 or 7, characterized in that: The temperature condition of the crystal growth treatment is 50°C-65°C, and the time of the crystal growth treatment is 9h-15h; and / or, The pH value of the environment for the crystal growth treatment is 2.0-4.0; and / or, In the crystal slurry, Li + The molar ratio of ferrous ion to ferrous ion is (0.98-1.08):
1.
9. The method according to claim 6 or 7, characterized in that: Further including: mixing the crystal nucleus solution with a reaction solution, wherein the reaction solution comprises an alcohol aqueous solution; and / or, A phosphate supplement is added to the crystal slurry, wherein the molar ratio of phosphate in the phosphate supplement to ferrous ions in the crystal slurry is (1-1.1):
1.
10. A positive electrode sheet, characterized in that: include: Positive electrode current collector; A positive electrode active material layer, the positive electrode active material layer is located on at least one side of the positive electrode current collector, and the positive electrode active material layer comprises the lithium iron phosphate material according to any one of claims 1 to 5.
11. A lithium battery, characterized in that: Including the positive electrode sheet as described in claim 10.
12. An electrical device, characterized in that: Including the lithium battery as claimed in claim 11.
Citation Information
Cited By
Lithium iron phosphate material and preparation method thereof, positive plate, battery and power utilization system
CN120793879A